Raster-scan optoacoustic mesoscopy in the 25-125 MHz range - Omar, Murad; Gateau, Jerome; Ntziachristos, Vasilis (Optics Letters, 2013)
We developed a raster-scan acoustic resolution broadband optoacoustic mesoscopy system and investigated the imaging performance using ultrasonic frequencies up to 125 MHz. The developed system achieves 7 m axial resolution and transverse resolution of 30 m reaching depths of at least 5 mm. This unprecedented performance is achieved by operating at out-of-focus ultrasonic detection and tomographic reconstruction. We demonstrate the limits reached due to the width of the laser pulse employed and showcase the technique on drosophila fly and drosophila pupae ex vivo. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-08